Looking for the earliest evidence of Ursus arctos LINNAEUS, 1758 in the Iberian Peninsula: the Middle Pleistocene site of Postes cave. (30th July 2021) - Villalba de Alvarado, Mónica; Collado Giraldo, Hipólito; Arsuaga, Juan Luis; Bello Rodrigo, José Ramón; van Heteren, Anneke H.; Gómez‐Olivencia, Asier
Abstract : Brown bears ( Ursus arctos ) diverged from the cave bear lineage c . 1.2 million years ago and likely originated in Asia, where the oldest fossils belong to a Middle Pleistocene chronology. Brown bear fossils from the Middle Pleistocene are scarce in the Iberian Peninsula, especially when compared to the cave bear record and they are mainly located in the southern half of the peninsula. The oldest evidence in the Iberian Peninsula is from c . 250 ka, which is 300 ka younger than the oldest European records ( 550 ka; L'Arago). Here we present the brown bear fossil assemblage from Postes cave (Fuentes de León, Extremadura, southern Iberian Peninsula). Postes cave has yielded some of the oldest evidence for brown bears in Iberia with a minimum date of 244 191±2261 a BP (number of identified specimens (NISP) = 4). Additionally, the uppermost part of the Pleistocene deposit has yielded one of the largest Middle Pleistocene brown bear collections in the Iberian Peninsula (NISP = 73) with a chronology roughly between 193 and 244 ka BP, comprising both cranial and postcranial remains and including a complete hemimandible. The Postes mandible fits well within the Middle Pleistocene brown bear range of variation, as it is significantly different in size and shape from the Holocene brown bears, based on geometric morphometric analyses. We show that these differences are due to allometry. This site provides more insight into the Middle Pleistocene morphological variation of brown bears in western Europe and underscores the need for additional Middle Pleistocene fossils in the northern half of Iberia to further test palaeobiogeographical hypotheses of this species' entrance into the largest of the southern European peninsulas.